The Global Poultry Agro/Food Complex - H. Constance , Douglas; D. Heffernan, William (The International Journal of Sociology of Agriculture and Food, 1991)
The globalization of the food system is a topic of growing concern as various nation/states try to obtain food security. This analysis test the hypothesis of the existence of a poultry agro/food complex being constructed by transnational corporations. We focus on the concept of "global sourcing" and argue that the rise in economic power of transnational corporations limits the abilities of individual nation/states to direct their agricultural policies toward national ends. We also argue that with the increasing transnational character of the large corporations the usefulness of individual nation/states or individual commodities as units of analysis decreases, We conclude that U.S., European, and Japanese transnational corporations are indeed creating a global poutry agro/food complex based on the concept of "global sourcing". Our findings also suggest that these same transnational corporations are very active in several other commodity sectors. Resumen El Complejo Global Agroalimentario Avícola La globalización del sistema alimentario constituye un aspecto que crecientemente concierne a varios estados/nación para lograr una verdadera seguridad alimentaria. El análisis parte de la hipótesis de la existencia de un sistema agroalimentario avícola, el cual ha sido construido por las corporaciones transnacionales. Nuestro foco de atención es el concepto de "recurso global", argumentando que el aumento del poder económico de las corporaciones transnacionales limita las posibilidades individuales de los estados/nación y apunta hacia el final de sus políticas agrícolas nacionales. Igualmente, que con el crecimiento del carácter transnacional de las grandes corporaciones existe una menor utilidad de los estados/nacián o de las mercancías, individualmente consideradas, y están perdienda valor como unidades de arálisis. Concluimos que las corporaciones transnacionales norteamericanas, europeas y japonesas están creando un verdadero complejo agroalimentario avícola, el cual esta basado en el concepto de "recurso global". Nosotros encontramos sugerencias de que estas mismas corporaciones transnacionales también son muy activas en otros importantes sectores de mercancías agrícolas.